The DIGITALIZATION OF MARKETING TOURISM PROMOTION IN BANDAR LAMPUNG CITY - Supriyanto Supriyanto; Putri Irmala Sari; Suripto Suripto (Metakom, 2021)
The Sky Arch is one of the new tourist attractions in the city of Bandar Lampung. This can be seen from the public's curiosity to come to visit Lengkung Langit. The achievement of Lengkung Langit in attracting public visits when it opened, was recorded as only 1,000 to 2,000 on weekend holidays. This study wants to know how the marketing of the digitalization of the promotional strategies carried out by the manager of the Lengkung Langit tourist spot. This study uses the Villa Gardenia tourist spot as a comparison. The data in this study were obtained by conducting interviews with the manager of Lengkung Langit and a little with Villa Gardenia. Observation and documentation are carried out for field proof. The visitors who were interviewed were only to cross-check the data from the interview with the manager. The results of this study indicate that the promotional strategy carried out by Lengkung Langit is in accordance with the marketing mix concept, by combining the 4 elements of P, namely product, price, place and promotions. Promotion using social media and digital media according to the demands of the times has been carried out by the management and owner of Lengkung Langit.